Principal Academic Supervision in Improving Teacher Performance at SD Negeri 004 Mundam, Dumai City - Dila Octaviani; Maya Novita Sari (Journal of Education and Teaching Learning, 2026)
This study examines the principal’s academic supervision in improving teacher performance at SD Negeri 004 Mundam, Dumai City. The research focuses on supervision planning, implementation approaches, and the impact of supervision on teacher performance. A qualitative case study was used with data from interviews, observation, and documentation involving teachers, the principal, and the school supervisor. The data were analyzed through condensation, reduction, presentation, and conclusion drawing. The findings show that supervision was planned through a clinical supervision schedule, checks on teaching documents, and annual teacher performance reports. Implementation used directive, non-directive, and collaborative approaches according to teacher typology. Follow-up was provided through rewards for good performance and guidance for teachers needing improvement. Academic supervision helped teachers identify weaknesses, improve teaching methods, strengthen discipline, and increase motivation to enhance learning quality